1997
DOI: 10.1002/(sici)1521-186x(1997)18:4<293::aid-bem1>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weak microwave fields amplitude modulated at ELF on EEG of symmetric brain areas in rats

Abstract: Averaged electroencephalogram (EEG) frequency spectra were studied in eight unanesthetized and unmyorelaxed adult male rats with chronically implanted carbon electrodes in symmetrical somesthetic areas when a weak (0.1–0.2 mW/cm) microwave (MW, 945 MHz) field, amplitude‐modulated at extremely low frequency (ELF) (4 Hz), was applied. Intermittent (1 min “On,” 1 min “Off”) field exposure (10‐min duration) was used. Hemispheric asymmetry in frequency spectra (averaged data for 10 or 1 min) of an ongoing EEG was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…Despite extensive research in the field of low-level microwave effects on the nervous system during recent decades (Johnson and Guy, 1972;Bawin et al, 1973;Baranski and Edelwejn, 1975;Gavalas-Medici and Day-Magdaleno, 1976;Chizhenkova, 1988;Mann and Roschke, 1996;Vorobyov et al, 1997;Wagner et al, 1998;Lutty et al, 2000), the reports of possible effects are often contradictory and the mechanisms behind the effects are still unclear. The difficulties in independent repeating of the experimental results cause doubt in these effects.…”
Section: Thermal and Non-thermal Effectsmentioning
confidence: 56%
See 1 more Smart Citation
“…Despite extensive research in the field of low-level microwave effects on the nervous system during recent decades (Johnson and Guy, 1972;Bawin et al, 1973;Baranski and Edelwejn, 1975;Gavalas-Medici and Day-Magdaleno, 1976;Chizhenkova, 1988;Mann and Roschke, 1996;Vorobyov et al, 1997;Wagner et al, 1998;Lutty et al, 2000), the reports of possible effects are often contradictory and the mechanisms behind the effects are still unclear. The difficulties in independent repeating of the experimental results cause doubt in these effects.…”
Section: Thermal and Non-thermal Effectsmentioning
confidence: 56%
“…Several investigators have reported that microwave exposure produces different alterations in the EEG signal: an increase in the number of slow rhythms in the EEG of rabbits (Chizhenkova, 1988), modulated at brain rhythm frequencies EMF affect EEG patterns in the cat (Bawin et al, 1973), a significant elevation of the EEG hemispheric asymmetry during the first 20 seconds of the stimulation period (Vorobyov et al, 1997).…”
Section: Thermal and Non-thermal Effectsmentioning
confidence: 96%
“…The reports of possible non-thermal effects are often contradictory. Several investigators have reported that low-level exposure produces alterations in the EEG signal and brain behavior (Bawin et al, 1973;Vorobyov et al, 1997;Mann et al, 1996;Wagner et al, 1998;Huber et al, 2000;Lass et al, 2002;Hinrikus et al, 2004). The conclusion reported by the other researchers is that the exposure to electromagnetic field does not alter the resting EEG (Hietanen et al, 2000;.…”
Section: Introductionmentioning
confidence: 89%
“…However, a close association between microwave and brain function has been identified and reviewed by D'Andrea et al 12 Available literature demonstrates the effects of different frequencies of microwave exposure of varied power densities on brain electrophysiology. 2,18,19,28,53 Agrawal 1 worked exclusively on chronic exposure of 1 kHz-modulated microwave frequency of 2450 MHz and examined the relationship between behavior and thyroid hormones of female rats. This study had suggested that chronic exposure of lowenergy-modulated microwave (2450 MHz) significantly affects hypothalamo-pituitary-thyroid axis, which finally results in alterations in behavior and concentration of thyroid hormone of the subjects.…”
Section: Discussionmentioning
confidence: 99%